Human trafficking involving marriage and partner migration to Australia - Kelly Richards
Abstract: In this report, what is known about human trafficking involving marriage and partner migration to Australia is described, drawing on primary information obtained from victim/survivor testimonies, stakeholder knowledge and expertise, and reported cases that progressed through the Australian justice system.  It confirms what some stakeholders in the human trafficking area have long suspected—that marriage and partner migration have been used to facilitate the trafficking of people into Australia